VIRTUAL SCREENING TO IDENTIFY POTENTIAL INHIBITOR OF ARGINASE OF LEISHMANIASIS - Sandesh Behera; Bhawani Prasad Bag (Journal of Biomedical and Pharmaceutical Research, 2020)
Leishmaniasis is caused by Leishmania protozoan parasites transmitted by the female phlebotomine sandfly. The current treatment regimen of leishmaniasis is not up to the mark and there is a huge scope of improvement. Hence, the need to approve new drugs, a complete understanding of the pathophysiology of the parasite is required. Since polyamines are required by the parasites for their infection cycle, inhibitors of polyamine pathway can be targeted by the new drugs for restricting the infection. In Leishmania, the polyamine biosynthetic pathway comprises of four compounds: arginase (ARG), ornithine decarboxylase (ODC), spermidine synthase (SPD), and S-adenosylmethionine decarboxylase (ADOMETDC). To identify these novel medicines like compounds, a structure-based screening system was utilized against downloaded drug-like compounds. In total, 1279 compounds were downloaded from the ZINC database dependent on the properties like the known inhibitor nor-NOHA [N(omega)- hydroxy-nor-L-arginase]. Virtual-ligand screening approaches were applied to identify drug-related like compounds utilizing sub-atomic docking program AutoDockVina in PyRx 0.8, and five best novel medication like compounds were chosen and their hydrogen ties with the receptor were decided.ZINC84057569, ZINC87440467, ZINC04617649, ZINC33978586, ZINC01677572 and ZINC35794928, ZINC33978586, ZINC84057569. ZINC53751324, ZINC00204059 were finalized as inhibitors against Human Arginase I and L. mexicana arginase individually contrasted with nor-NOHA, based on their binding efficiency. These inhibitors may become the base for formulating new drugs against Leishmania’s, focusing on both the protein for example Human Arginase I and L. mexicana arginase. Keywords: Leishmaniasis, Human Arginase I, Leishmania mexicana arginase, nor-NOHA, Polyamine pathway, Molecular docking, Virtual screening.